Adsorption Of Lead (II) From Aqueous Solution By Activated Carbon Developed From Mangrove Wood By Microwave Radiation Heating - Tan Lekha @ Malek, Hajar (Universiti Sains Malaysia, 2021)
Activated carbon is an adsorbent that is large in surface area with a great amount of porous structure formed on it. Activated carbon is utilised as an adsorbent because of the effectiveness for adsorbing a wide type of contaminants in liquids or gases. This study aims to develop an activated carbon derived from the mangrove wood to adsorb heavy metal which is lead (II) ions. The adsorbent was activated via physical activation by microwave heating and gasification of nitrogen (NO2). Study on the effects of the operating condition on the activation of the adsorbent was performed by exposing the char at different radiation time and radiation power. The optimization of the activated carbon was performed by using response surface methodology (RSM). The optimum condition obtained for the prepared activated carbon was at radiation time of 2 minutes and radiation power of 528.66 watt. Removal of lead (II) ions in batch system was performed by investigating several parameters such as initial lead (II) ions concentration, contact time, solution temperature and solution pH In this studies, the highest removal of lead (II) ions in a batch system was at pH 4, initial lead concentration of 10 mg/L and the optimum contact time of 30 minutes. The isotherm studies were performed and the results show that the adsorbate-adsorbent system fitted well to the Langmuir isotherm model compared to Freundlich isotherm model. In this study, the adsorption reaction performed by using activated carbon prepared from mangrove wood was found to be effective in removing high percentage of lead (II) ions.